Analisis Sentimen Masyarakat Sebelum Dan Sesudah Terpilihnya Gibran Sebagai Cawapres Prabowo Menggunakan Naïve Bayes - Alfito Gaizka; Achmad Rizal Dzikrillah; Estu Sinduningrum (STMIK Budi Darma, 2024)
The presidential and vice presidential elections in Indonesia always trigger debate, especially in 2024 which is considered quite grabbing public attention. The latest controversy arose regarding Gibran's candidacy as Prabowo's running mate. This study aims to analyze changes in public sentiment before and after Gibran was selected as a vice presidential candidate in reviews on the Twitter (X) application. The dataset used in this study is a review from Twitter (X) with a period of time from July 2023 to December 2023, or before and after Gibran's nomination as Prabowo's vice president, then the dataset is saved into a csv file into GibranSebelum, GibranSesudah, PrabowoSebelum, dan PrabowoSesudah. The dataset was then analyzed using the Naïve Bayes algorithm by classifying sentiment into positive and negative categories. The Preprocessing stages carried out in this study include Cleansing, Tokenizing, Stopwords, and Transform Cases. This study also used the confusion matrix evaluation method to measure accuracy using three parameters, namely accuracy, precision, and recall. The results showed variations in model performance, GibranSebelum's dataset achieved 42.86% accuracy, 20.00% precision, and 100.00% recall, while GibranSesudah produced 67.80% accuracy, 52.50% precision, and 100.00% recall. PrabowoSebelum's dataset recorded 60.71% accuracy, 44.07% precision, and 100.00% recall, while PrabowoSesudah had 55.00% accuracy, 35.71% precision, and 100.00% recall. Analysis shows a trend of increasing negative sentiment after Gibran was sworn in as Prabowo's vice president, signaling an increase in public dissatisfaction with the condition